Can't Stop Korean with K-Pop : The Fun, Effective Way to Learn the Korean Language - Kang, Peter (Createspace Publishing, 2016)
Made for the Korean language student or the K-pop fan. Learn and improve your Korean with K-pop. Translations are explained and made accessible. The songs are selected for learning usefulness and organized by grammar. BTS, Big Bang, Girls' Generation, Twice, Black Pink, EXO, Infinite and other favorites. Your favorite songs- Overdose, I Got A Boy, Cheer Up, Loser, Fire, Playing with Fire, Russian Roulette, Gee and more. Whether you are a student of Korean or simply a K-pop fan who wants to understand- this book is for you. As a fan, you'll get to understand the real meaning of the lyrics that take you into the heart of K-pop. You'll see what makes each group unique and why their fans are fanatical. For the beginning Korean student, you'll get introductory grammar and a Korean alphabet section- enough to get started. Experienced students will improve with the translation and notes that guide you through the lyrics. Repetitive listening via Youtube and other outlets will help you get accustomed to the very different syntax, grammar, and phonics that is Korean. With time, Korean can become second nature thru the power of music.